STUDI KETENAGAKERJAAN JAWA TENGAH : ANALISIS DATA BADAN PUSAT STATISTIK AGUSTUS 2021 – AGUSTUS 2023 - Arif Firmansyah; Bambang Agus Herlambang, Ahmad Khoirul Anam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Employment is one of the main concerns of the Central Java Provincial Government. The aim of this research is to determine employment conditions in Central Java using several indicators. The research results show that although Central Java's TPAK has increased from year to year, the difference between men's and women's TPAK is still large. TPT for men is higher than TPT for women, and urban TPT is higher than rural TPT. The TPT for Vocational High School (SMK) graduates is always the highest, compared to the TPT for graduates of other levels of education. Based on main employment status, the working population can be categorized into formal and informal activities. Residents who work in formal activities include those who work with the help of permanent workers and workers/employees/employees, while the rest are categorized as informal activities (self-employed, businesses assisted by temporary workers/unpaid workers, casual workers, and family/unpaid workers ).